2007
DOI: 10.1113/expphysiol.2007.038190
|View full text |Cite
|
Sign up to set email alerts
|

Isotonic contractile impairment due to genetic CLC‐1 chloride channel deficiency in myotonic mouse diaphragm muscle

Abstract: The hallmark of genetic CLC-1 chloride channel deficiency in myotonic humans, goats and mice is delayed muscle relaxation resulting from persistent electrical discharges. In addition to the ion channel defect, muscles from myotonic humans and mice also have major changes in fibre type and myosin isoform composition, but the extent to which this affects isometric contractions remains controversial. Many muscles, including the diaphragm, shorten considerably during normal activities, but shortening contractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 40 publications
5
12
0
Order By: Relevance
“…The choice of using peak force during 20 Hz stimulation rather than tetanic force to define maximum load was based on two considerations. First, it is consistent with the approach used in our previous studies of muscle isotonic contractile properties [30,31]. Second, the present study was performed in the context of functional electrical stimulation, and thus it is more meaningful to base loads on force produced during the frequency at which the muscle will be stimulated.…”
Section: Methodssupporting
confidence: 56%
“…The choice of using peak force during 20 Hz stimulation rather than tetanic force to define maximum load was based on two considerations. First, it is consistent with the approach used in our previous studies of muscle isotonic contractile properties [30,31]. Second, the present study was performed in the context of functional electrical stimulation, and thus it is more meaningful to base loads on force produced during the frequency at which the muscle will be stimulated.…”
Section: Methodssupporting
confidence: 56%
“…The latter issue has been examined to a limited extent in a previous study from our lab in which we examined isotonic contractions of diaphragm muscle from genetically myotonic mice [19]. Diaphragm from these mice had lesser degrees of myotonia than seen in the diaphragm of the present study.…”
Section: Discussionmentioning
confidence: 70%
“…Peak force was defined as the largest value that occurred during the portion of the contraction while the muscle was being electrically stimulated (and thus did not include mechanical myotonia even if mechanical myotonia exceeded force during active electrical stimulation). These force values were normalized relative to twitch force before drug addition to factor out the effects of variability among muscle samples in absolute force related to variability in animal size and muscle sample size, similar to previous studies of a similar nature [11,15,19,22]. Contraction time was defined as the time from the onset of force production to the top of the first peak of the non-fused contraction; values for contraction time are not presented in those instances in which a distinct first peak was not discernable (which was the case for 50 Hz stimulation for the diaphragm).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, toxicity studies showed that statin therapy plus eccentric exercise stress enable muscle instability, triggering stronger activation of intracellular proteolytic cascades (Urso et al, 2005). At this regard it is known that the mechanical stress during exercise may aggravate ClC-1 function (van Lunteren et al, 2007; Camerino et al, 2014b; Cozzoli et al, 2014) and that the activation of Ubiquitin Ligase Complex specifically mediates the poly-ubiquitination and degradation of ClC-1 (Chen et al, 2015). At the light of these findings, it would be also important to verify if strenuous exercise and/or genetic mutations of ClC-1, may potentiate adverse effects of statins, as already observed for metabolic myopathies (Tay et al, 2008).…”
Section: Discussionmentioning
confidence: 99%